TRADISI TUKAR CINCIN KHITBAH DALAM WACANA KEISLAMAN KONTEMPORER - Sawaluddin Siregar; Maryam Dalimunthe; Surya Drajat Hasibuan (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2025)
This article examines the phenomenon of exchanging rings in the khitbah (proposal) process as part of Muslim wedding traditions in contemporary society. This practice is deeply rooted in local culture, but it still raises questions from an Islamic legal perspective: is it permissible according to Islamic law, or does it contain elements of tasyabbuh (imitation) of non-Islamic cultures? This study uses a qualitative approach with field research methods, conducted in Selawan Village, North Sumatra. Data was collected through observation, in-depth interviews with couples, religious leaders, and traditional leaders, as well as documentation of the khitbah procession in the community. The results of the study show that the tradition of exchanging rings is seen as a symbol of commitment, but it does not have an explicit basis in Islamic law. Some religious leaders view this practice as a custom that is permissible as long as it does not contain elements contrary to Islamic principles, such as extravagance (israf) or deviant beliefs. This tradition reflects the dialectic between culture and religion, and highlights the need for a contextual approach in responding to the symbolic dynamics of modern Muslim life. This study offers an integrative perspective between customary values, fiqh muamalah, and Islamic ethics in understanding evolving socio-religious practices.